Body fat percentage is a better marker than body mass index for determining inflammation status in polycystic ovary syndrome - Andon Hestiantoro; Rachmat Dediat Kapnosa Hasani; Amalia Shadrina; Herbert Situmorang; Nurul Ilma; Raden Muharam; Kanadi Sumapraja; Budi Wiweko (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Polycystic ovary syndrome (PCOS) is an endocrinopathic disorder most commonly experienced by women of reproductive age, and it is characterized by a low-grade chronic inflammatory condition. Excessive fat deposit has been long considered as an etiological factor in the pathogenesis of this inflammatory condition. Currently, body mass index (BMI) or percentage of body fat is used as a marker to assess the body fat composition of a person. Objective: To determine whether BMI or body fat percentage (BFP) can be used as a better marker for measuring inflammation related to body fat accumulation in polycystic ovary syndrome patients. Materials and Methods: This study took place at the Center for Reproductive Medicine, Yasmin Clinic, Cipto Mangunkusumo Hospital from January to December 2015. In this cross-sectional study, 32 reproductive age women with PCOS according to the Rotterdam criteria (2003) participated. Women with hyperandrogenism caused by non-classic congenital adrenal hyperplasia, pregnant and lactating women, etc., were excluded. Some variables such as BMI, clinical hyperandrogenism sign, BFP, and inflammatory markers were assessed and statistically analyzed. Results: From a total of 32 subjects of the study, BFP had a significant positive correlation with procalcitonin levels (r=0.35; p=0.048), while BMI did not (r=0.27; p=0.131). Conclusion: BFP can be used as a better marker for measuring inflammation related to body fat accumulation in PCOS subjects.